Inkluzje i ekskluzje podmiotu w zbiorze Bez ciebie Anny Augustyniak - Wądolny-Tatar, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The main concept of Anna Augustyniak’s poetic volume (Bez ciebie, Warsaw 2014) is based on poetics and semantics of a number of categories: deficiency, body, affection, journey. They make an entanglement, which shows the metamorphosis of feminine lyrical subject, at first being mentally, emotionally and sensually disconnected (excluded by itself) from the environment though love, later again connected with world through the journey in geographically-cultural and spiritual dimension. In this case, the strong affection (falling in it and out of it after the parting) can be treated analogously. Construction and titles of several poems included in volume create an enumerative series describing the condition of subject (condition “without”), both as addiction and as deliverance, inclusion and exclusion. “Traveling erotics” – as Alicja Jakubowska-Oż.g named these poems – are also an individual realisation of a convention of literary genetics. A poem appears as a body of inclusion, which encloses a story of love.